2007
DOI: 10.1016/j.orggeochem.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons and polychlorinated biphenyls in urban soils from Kathmandu, Nepal

Abstract: Kathmandu, the capital of Nepal, faces increasing environmental problems such as heavy air pollution and lack of proper waste management. The aim of this study was to examine if the soils are also affected by pollution, with the focus on polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs). The sum of 20 PAHs in surface soils ranged between 184 and 10279 lg kg À1 . The most abundant PAHs were perylene (14.6%), benzo(b+j+k)flouranthene (10.7%), naphthalene (10.7%) and phenanthrene (9.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 45 publications
2
58
2
1
Order By: Relevance
“…Most of the polycyclic aromatic hydrocarbons (PAHs) in the environment originated from incomplete combustion processes such as fossil fuel combustion, biomass burning, volcanoes, and wildfires (Aichner et al 2007;Liu et al 2014). PAHs are also resulted from petroleum products or oil spills as secondary sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the polycyclic aromatic hydrocarbons (PAHs) in the environment originated from incomplete combustion processes such as fossil fuel combustion, biomass burning, volcanoes, and wildfires (Aichner et al 2007;Liu et al 2014). PAHs are also resulted from petroleum products or oil spills as secondary sources.…”
Section: Introductionmentioning
confidence: 99%
“…PAHs are lipophilic chemicals that are prone to adsorb onto soil particles. Consequently, soil serves as a PAH source and sink in urban areas, accumulating PAHs from processes such as atmospheric deposition and water irrigation (Aichner et al 2007;Bu et al 2009). The characteristics of PAHs in urban soils have been helpful in understanding the long-term history of pollution and their connection with urbanization and industrialization Peng et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the LRAT of PAHs has been studied in remote mountainous regions (Elliott et al, 2012;Aichner et al, 2007). The main source of PAHs in the mountains is deposition from the atmosphere (Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the Himalayas have indicated that PAHs emitted in Nepal and India may be transported by the Southern Asian monsoon along valleys from the Indian Subcontinent to the Himalayas (Kang et al, 2009). It has been reported that concentrations of PAHs in soils of Nepal (184e10,279 ng/g, dry weight (dw)) (Aichner et al, 2007) were greater than those reported in northern slope of the CentralHimalayas on the TPC (5.5e62.2 ng/g, dw) . The concentration of PAHs in soils might pose risks to the ecosystem of the Himalayas, which is also an important source of freshwater for as much as one sixth of the world's population (including China, India and Nepal) (Loewen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first time multivariate statistical tool is used for purposes of source apportionment within the subsaharan tropical coastal environment. Fluxes of PAHs have been increasing within the past decades with their attendant health risk (Van Metre et al, 2000;Schneider et al, 2001;Lima et al, 2003;Walker et al, 2005;Aichner et al, 2007;Scholz-Bottcher et al, 2009), necessitating the identification of the sources of these compounds in the present study. As PAHs released in the study area may be globally distributed, knowledge of PAH sources in this tropical environment is a prerequisite for understanding the global PAH dynamics.…”
Section: Introductionmentioning
confidence: 99%